New Developments in Quantitative Psychology Presentations from the 77th Annual Psychometric Society Meeting - Millsap, Roger E.; van der Ark, L. Andries.; Bolt, Daniel M.; Woods, Carol M. (Springer Proceedings in Mathematics & Statistics,, 2013)
The 77th Annual International Meeting of the Psychometric Society (IMPS) brought together quantitative researchers who focus on methods relevant to psychology.  The conference included workshops, invited talks by well-known scholars, and presentations of submitted papers and posters. It was hosted by the University of Nebraska-Lincoln and took place between the 9th and 12th of July, 2012. The chapters of this volume are based on presentations from the meeting and reflect the latest work in the field.   Topics with a primarily measurement focus include studies of item response theory, computerized adaptive testing, cognitive diagnostic modeling, and psychological scaling.  Additional psychometric topics relate to structural equation modeling, factor analysis, causal modeling, mediation, missing data methods, and longitudinal data analysis, among others.   The papers in this volume will be especially useful for researchers (graduate students and other quantitative researchers) in the social sciences who use quantitative methods, particularly psychologists.  Most readers will benefit from some prior knowledge of statistical methods in reading the chapters.